2023
DOI: 10.1088/2053-1591/acb908
|View full text |Cite
|
Sign up to set email alerts
|

Influence of filler wire on metallurgical, mechanical, and corrosion behaviour of 430 ferritic stainless steel using a fusion welding process

Abstract: The advantage of ferritic stainless steels (FSS's) over austenitic stainless steels is that they are less expensive alloys. This is due to low or negligible nickel in its alloying element which makes the steel affordable. This type of steel is highly recommended against chloride attack and is also machinable to produce various components for engineering applications. This study examines the effect of various fillers on 430 ferritic stainless steel (FSS). The austenitic (308) and ferritic (410) grades of filler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…In addition, Bhadeshia and Honeycombe [39] explained the relationship between the carbon content and hardness of martensite, and that an appropriate carbon content results in suitable hardness results. Studies by Araújo et al [40] and Bansod et al [41] reported hardness values in the fusion zone with ER308L and 308 filler wires, which presented results similar to those verified in the present work. Hardness values of approximately 175, 182, and 180 HV of the 70A-ER308L fusion zone [26] were higher than those of the 70A-ER309L and 100A-ER309L fusion zones.…”
Section: Hardness and Tensile Propertiessupporting
confidence: 91%
“…In addition, Bhadeshia and Honeycombe [39] explained the relationship between the carbon content and hardness of martensite, and that an appropriate carbon content results in suitable hardness results. Studies by Araújo et al [40] and Bansod et al [41] reported hardness values in the fusion zone with ER308L and 308 filler wires, which presented results similar to those verified in the present work. Hardness values of approximately 175, 182, and 180 HV of the 70A-ER308L fusion zone [26] were higher than those of the 70A-ER309L and 100A-ER309L fusion zones.…”
Section: Hardness and Tensile Propertiessupporting
confidence: 91%
“…Austenitic stainless steels are the most widely used metal due to its important and superior properties like ductility, drawability, strength, toughness, wear resistance, fabricability, corrosion resistance etc.. [1], [2] It has applications in many industries like tableware, pipes, pressure vessel, biomedical implants etc. [3]- [6] Some applications like steam generating plants, superheating tube materials is because of its elevated temperature properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ferritic Stainless Steels (FSSs) have acquired recognition in industrial use due to their high resistance to wear [1]. They are cheap and exhibit high formability compared to their austenitic equivalents [2]. FSSs also demonstrate enhanced thermal conductivity, making them appropriate for high-temperature applications [3].…”
Section: Introductionmentioning
confidence: 99%